The Childfree Phenomenon Based on Islamic Law and Its Respond on Muslim Society - Jafar, Wahyu Abdul; Zulfikri, Zulfikri; Sadiqin, Amin; Jayadi, Usman; Suriyani, Irma (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This study aims to determine the cause of married couples choosing the childfree trend and to describe the impact of the development of the childfree trend in Muslim society. In addition, this study also aims to learn about childfree law from the perspective of Islamic law in various perspectives. This study is field research. The data collection technique in this research is using a survey. Respondents in this study amounted to 215 people. Based on the survey results, several significant findings related to the childfree phenomenon were found, among others: the factors that most influence married couples to choose the childfree trend are economic factors as much as 42% and health factors as much as 21.5%. The majority of informants, as much as 54%, stated that the childfree phenomenon might impact the social life of the Muslim community. The conclusion of the childfree law on the grounds of economic and social factors is that it is forbidden. Likewise, childfree use of permanent types of contraception is illegal. The childfree for reasons of health and trauma factors (psychological disorders); the law is permissible. Public rejection of the childfree trend due to economic factors is around 56.3%. Meanwhile, the community's rejection of the childfree trend for reasons to be happier is around 76.2%.